Comunicación familiar y su incidencia en la conducta de los estudiantes de segundo de bachillerato paralelos a y b de la unidad educativa América en la ciudad de Quevedo, provincia de los Ríos - Paredes Colorado, Claudia Elizabeth (2015)
Communication is an act that can inform others what we feel, think and do, this is the effective means to interact with society and make known who we are. Through communication they are obtained great benefits such as: avoid reaching discussions and the best way to solve things. Home communication represents the basis where the family is held; as long as there is more communication, there will also be improvements in family relationships. In many households difficult situations because of the lack or miscommunication that there are living, believing that talk, advise or speak create a wide and effective relationship with his family but this is one of the mistakes that almost everywhere is committed and usually they end up being affected teenagers because on stage they are have low frustration tolerance and therefore are susceptible to changes. This research has been created to guide and indicate effective in improving the communication relationships in the family and benefit in this way adolescents who suffer the consequences, changing their behavior to not feel supported by these authority figures techniques.